Aplikasi Gambar Berseri untuk Meningkatkan Kemampuan Menulis Naratif dalam Pembelajaran Bahasa Inggris pada Siswa Kelas XI IPA 5 SMAN 5 Bandar Lampung - Noviati, Endang Tri (STKIP PGRI Bandar Lampung, 2020)
The purpose of this study is to describe the improvement of learning outcomes in narrative writing in English. This research was conducted at SMA Negeri 5 Bandar Lampung kls XI IPA 5 semester 2. The research was carried out in 3 cycles, each cycle consisting of 4 stages, namely planning, implementing, observing and reflecting. Research indicators for student activities are if 90% of students are already active in learning activities, while indicators for student learning outcomes are if 85%; students have received a minimum score of 70 in accordance with the Minimum Completeness Criteria. The results showed that: (1) In cycle I, only 50% of students were active in learning activities, the activities of these students increased to 100% in cycles II and III. (2) Learning outcomes also show an increase. In the first cycle, only 39% of students had reached a value of 70. This learning outcome increased in cycle II to 74% and in cycle III 92%.